1,1,2,2-Tetramethyl-1,2-disilacycloocta-3,7-diyne: structure and bonding properties of a highly strained cyclic diyne - Haberhauer, Gebhard; Rominger, Frank; Gleiter, Rolf (Perkin, 1999)
1,1,2,2-Tetramethyl-1,2-disilacycloocta-3,7-diyne (4) could be prepared by reaction of 1,8-dibromo-4,4,5,5-tetramethyl-4,5-disilaocta-2,6-diyne (9) with lithium in the presence of catalytic amounts of biphenyl. X-Ray investigations on single crystals of 4 revealed an almost planar structure adopting C2v symmetry. The transannular distances between the pairs of carbon atoms in the triple bonds are 2.672 and 3.153 Å, respectively. The analysis of the He(I) photoelectron spectrum of 4 reveals a strong interaction between the in-plane π-orbitals of the triple bonds and the Si-Si σ-bond.